Recent release from prison — A novel risk factor for intimate partner homicide. Issue 1 (January 2021) - Cirone, Justin; Keskey, Robert; Hampton, David; Slidell, Mark; Crandall, Marie; Rattan, Rishi; Velopulos, Catherine G.; Allen, Debra; Williams, Brian H.; Wilson, Kenneth; Zakrison, Tanya L.
Abstract : BACKGROUND: The United States has the highest per-capita incarceration rate and the largest prison population in the world. More than two thirds of recently incarcerated individuals will be arrested again within 3 years of release and may commit crimes as serious as homicide soon after discharge. The pattern of homicidal violence currently remains unknown for recently incarcerated homicide suspects (RIHS) and their victims. METHODS: A retrospective analysis of the 36 states included in the 2003 to 2017 National Violent Death Reporting System was performed with a focus on RIHS and their victims. Pearson χ 2 and Wilcoxon rank sum tests were used for comparison. RESULTS: There were 249 RIHS in the database of the 14, 561 homicides where suspect recent incarceration status was documented. Compared with not–recently incarcerated suspects, RIHS were more likely to be White (41% vs. 29%, p < 0.001) and male (97% vs. 91%, p < 0.001). Recently incarcerated homicide suspects more often had a known relationship with the victim (75% vs. 51%, p < 0.001), and these homicides more often occurred in the victim's own home (43% vs. 34%, p = 0.006). Intimate partner violence was a factor in 31% of the RIHS cases (vs. 17%, p < 0.001). The homicide weapon was most likely to be a firearm (57.8%, p < 0.001). Only 6.4% of homicides were due to mental health illness. Gang violence, while more common in the RIHS group, was still only a precipitating factor in 12.0% of the homicides (vs. 7.4%, p = 0.006). CONCLUSION: Recently incarcerated homicide suspects are more likely to kill a known person in their own home with a firearm, and these homicides are frequently categorized as intimate partner homicides. Gang violence and mental health are not frequent precipitating factors in these deaths. Additional future interventions are urgently needed to eliminate these preventable deaths by alerting previous or current intimate partners of those being discharged from the prison system.